A Case of a Ruptured Sclerosing Liver Hemangioma - Haris Papafragkakis; Martin Moehlen; Monica T. Garcia-Buitrago; Beatrice Madrazo; Eddie Island; Paul Martin (International Journal of Hepatology)
Hemangiomas are the most common benign tumors found in the liver, typically asymptomatic, solitary, and incidentally discovered. Although vascular in nature, they rarely bleed. We report a case of a 52-year-old woman with a previously stable hemangioma who presented to our hospital with signs and symptoms indicative of spontaneous rupture. We review the literature, focusing on diagnosis and management of liver hemangiomas.